The madhouse effect how climate change denial is threatening our planet, destroying our politics, and driving us crazy - Mann, Michael E. 1965-; Toles, Tom 1951- (Columbia University Press, 2016)
The award winning climate scientist Michael E. Mann and the Pulitzer Prizewinning political cartoonist Tom Toles have fought at the frontlines of climate denialism for most of their careers. They have witnessed the manipulation of the media by business and political interests and the unconscionable play to partisanship on issues that affect the well-being of millions. The lessons they have learned have been invaluable, inspiring this brilliant, colorful escape hatch from the madhouse of the climate wars. Through satire, The Madhouse Effect portrays the intellectual pretzels into which denialists must twist logic to explain away the clear evidence that man-made activity has changed our climate. Toles's cartoons collapse counter-scientific strategies into their biased components, helping readers see how to best strike at these fallacies. Mann's expert skills at science communication aim to restore sanity to a debate that continues to rage against widely acknowledged scientific consensus. The synergy of these two commonsense crusaders enlivens the gloom and doom of so many climate-themed booksand may even convert a few of the faithful to the right side of science